2009
DOI: 10.1111/j.1574-6968.2009.01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Folate overproduction inLactobacillus plantarumWCFS1 causes methotrexate resistance

Abstract: Folate overproduction can serve as a mode of resistance against the folate antagonist methotrexate in Lactobacillus plantarum WCFS1. When compared with a wild-type control strain, an engineered high folate-producing strain was found to be insensitive to methotrexate. The growth rate and the viable count of the folate-overproducing L. plantarum strain were not significantly affected by the presence of methotrexate in the growth medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Secondly, specific analyses were performed to determine mechanisms that cause the observed growth rate reduction upon folate overproduction. Previously it was shown that homologous overexpression of the folate gene cluster of L. plantarum results in high folate pools [18]. It was shown that there is 55-fold more folate produced in L. plantarum cultures harboring plasmid pNZ7026 (which carries all genes in the folate biosynthesis pathway) when compared to the control strain carrying plasmid pNZ7021 (empty expression vector) [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, specific analyses were performed to determine mechanisms that cause the observed growth rate reduction upon folate overproduction. Previously it was shown that homologous overexpression of the folate gene cluster of L. plantarum results in high folate pools [18]. It was shown that there is 55-fold more folate produced in L. plantarum cultures harboring plasmid pNZ7026 (which carries all genes in the folate biosynthesis pathway) when compared to the control strain carrying plasmid pNZ7021 (empty expression vector) [18].…”
Section: Resultsmentioning
confidence: 99%
“…Previously it was shown that homologous overexpression of the folate gene cluster of L. plantarum results in high folate pools [18]. It was shown that there is 55-fold more folate produced in L. plantarum cultures harboring plasmid pNZ7026 (which carries all genes in the folate biosynthesis pathway) when compared to the control strain carrying plasmid pNZ7021 (empty expression vector) [18]. Using differential metabolomics it was determined whether specific metabolites were more or less abundant in L. plantarum harboring pNZ7026 in comparison to L. plantarum carrying the control plasmid pNZ7021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it has been shown that L. plantarum WCSF1, a commensal Lactobacillus strain isolated from human saliva, was shown to possess the folate biosynthesis genes in its genome [45] and that this strain can produce folate in culture media [46]. However, it was shown that only one genetic modification allowed this strain to produce enough of the vitamin to generate a methotrexate (a folate antagonist) resistant phenotype that is observed in high-folate producing strains [47]. Also, it was shown that the riboflavin biosynthesis operon has been shown to be interrupted in L. plantarum WCFS1 genome resulting in its inability to produce riboflavin or other vitamins [45].…”
Section: The Key Role Of Vitamins Produced By Commensal and Probioticmentioning
confidence: 99%
“…There is a long history of the application of LAB in a variety of fermentation processes, but especially in the last three decades interest in LAB has significantly increased since many strains, mostly members of the genus Lactobacillus , have health-promoting properties (25). In addition, many LAB strains are robust organisms that are able to withstand harsh conditions such as ethanol and stomach acid, which makes them attractive vehicles for the development of industrial producer strains and biotherapeutics, respectively (614). Taken together, LAB are therefore the most abundant group of Gram-positive bacteria used in industry and medicine representing a major economic factor.…”
Section: Introductionmentioning
confidence: 99%